Practice patterns and perspectives regarding treatment for symptoms of menopause: qualitative interviews with US health care providers. Issue 2 (20th February 2023) - DePree, Barbara; Houghton, Katherine; DiBenedetti, Dana B.; Shiozawa, Aki; King, Deanna D.; Kim, Janet; Mancuso, Shayna
Abstract : US healthcare providers reported prescribing therapies for menopausal symptoms and noted that these therapies were perceived as generally effective; however, barriers to initiation of prescription therapy exist and new treatment options are needed. Abstract: Objective: To document health care providers' views regarding treatments for symptoms associated with menopause and discussions with patients about symptoms and treatment decisions. Results informed development of a data collection form for a retrospective medical record review (reported separately). Methods: Registered US gynecologists or primary care providers from all US regions were identified from local association directories and an in-house database and were invited to participate in a qualitative interview if they consulted with three or more patients per week presenting with menopausal symptoms. Participants provided demographic data, information about patients' symptoms, and health care provider and patient views on prescription and nonprescription therapies. Key concepts/themes from interviews were identified. Results: Participating health care providers (10 gynecologists, 10 primary care providers) agreed there are effective treatment options for menopausal symptoms, particularly vasomotor symptoms and vaginal dryness and/or atrophy. Health care providers reported that treatment was generally dictated by symptoms that interfered with quality of life and/or daily activities, although patients often had symptoms for months before presentation. All health care providers said they prescribe hormone and/or nonhormone therapies for treatment of menopausal symptoms; half stated that they typically inquire about patients' nonprescription therapy use, and 45% recommend specific nonprescription therapies. The most commonly cited barriers to initiation of any therapy for menopausal symptoms were patient concerns about risks and financial considerations (ie, insurance or cost). Conclusions: US health care providers reported prescribing therapies for menopausal symptoms and noted that these therapies were perceived as generally effective; however, barriers to initiation of prescription therapy exist, and new treatment options are needed.